2020
DOI: 10.1002/zoo.21584
|View full text |Cite
|
Sign up to set email alerts
|

Bearing fruit: Piloting a novel judgment bias task in an American black bear

Abstract: Judgment bias tasks can reveal changes in affect in animals as a function of environmental manipulations such as provision of enrichment. We assessed affect in an American black bear across seasonal changes in availability of a mulberry bush. We used a novel judgment bias task in which the background color of a touchscreen signaled whether the left or right positioned stimulus was correct. The bear learned the conditional rule in which the correct action for the white background (choose left) resulted in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Our results add to the literature suggesting that touchscreen images are seen as representing real food items [10,20,21,[27][28][29][30]. Primates in previous studies demonstrated transfer of preferences from trained stimuli to novel images of the same food, indicating that they represented the images as depicting particular foods [19].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our results add to the literature suggesting that touchscreen images are seen as representing real food items [10,20,21,[27][28][29][30]. Primates in previous studies demonstrated transfer of preferences from trained stimuli to novel images of the same food, indicating that they represented the images as depicting particular foods [19].…”
Section: Discussionsupporting
confidence: 78%
“…These findings suggest that presentation of food items using images presented on touchscreen computers may be a valid way to assess food preferences, at least in primates and other species with similar visual systems. Other work suggests that it is also a valid method for testing food preferences in bears [21,28,29]. We have gone beyond previous work to show that the method can be validated both through comparison to choices of actual food items and preferences for images of preferred food items when paired with randomly selected images of less preferred foods.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that the nature of the task itself-requiring a conditional discrimination-rather than a failure of the representational nature of the categories of preferred and less preferred foods, led to the gorillas' difficulty. While assessing optimism and pessimism in the same gorillas using a novel judgment bias task that also required a conditional discrimination (i.e., if black background, choose right, if white background, choose left), the gorillas also struggled to learn the discrimination (McGuire & Vonk, 2018) although it was mastered by a black bear in fewer than 100 trials (Vonk et al, 2021). Furthermore, Bernstein-Kurtycz et al (n.d.) presented a version of the same task to two brown bears and one bear also learned the discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…When the gorillas were trained to receive three versus one piece of a biscuit when selecting images that represented the same amounts of biscuit, they chose more randomly than when presented with a choice of three versus one actual pieces of biscuit (McGuire & Vonk, 2018). Once again, a black bear tested in a similar task showed better evidence of understanding that selecting images of a larger quantity of food led to receiving a larger quantity (Vonk et al, 2021). Coupled with other gorillas' poor discrimination of images of bananas versus actual bananas (Perron et al, 2008), it is possible that gorillas are not the ideal candidates for procedures that require them to use visual stimuli to represent real objects.…”
Section: Discussionmentioning
confidence: 99%